“Byronic” Phraseological Units and Their Equivalents in the Armenian Translation - Poghosyan, Ofelya; Ghumashyan, Varduhi (Armenian Folia Anglistika, 2018)
The article highlights one of the most typical features of G.G. Byron’s individual style, particularly, the use of a great variety of phraseological units in his works. The basic layer of Byron’s literary vocabulary includes phraseological units derived from the Bible and Greek mythology. The present article focuses on the problem of translatability of the so-called “Byronic” phraseological units in his narrative poem Childe Harold’s Pilgrimage. It is an acknowledged fact that Byron’s works are translated into numerous languages and the Armenian translations have their special place among them. The eminent Armenian writer H.Tumanyan succeeded in finding the best equivalents of “Byronic” phraseological units that not only sound convincing, truthful and colourful, but also very often enrich both the source and the target languages.